Treatment of anaerobically digested palm oil mill effluent (POME) using JERING (Archidendron jiringa) seeds as a novel plant-based coagulant - Xavier, Deeviya Francis (2017)
The main aim of this work is to investigate the potential of unmodified plant-based coagulants and flocculants in the treatment of anaerobic POME. The focus of this research is to study jering (archidendron jiringa) seeds and their potential as a coagulant in the treatment of anaerobic POME. The use of synthetic coagulants in the industry has caused detrimental effects to the environment. Therefore, an environmental friendly and cost-effective material is required as a replacement. Since the effectiveness of jering seeds as a coagulant has not been evaluated previously, this study represents the discovery of a plant-based coagulant applicable in anaerobic POME treatment. Using technologies such as SEM, BET, FTIR, Zeta potential and EDX, the characteristics and surface properties of the jering seeds have been successfully identified and compared with the more established coagulant, moringa oleifera seeds in order to have a clearer observation on the coagulating properties of jering seeds. Coagulation and flocculation studies were carried out by means of a jar test. The optimised coagulant dosage of 1.0g/L, flocculant dosage of 0.1g/L, pH of 5, flocculation mixing rate of 20rpm and coagulation mixing rate of 300rpm resulted in a maximum reduction in total suspended solids (TSS) removal (73.3%) and turbidity removal (71.6%). Data selected for all the experiments conducted in this study were determined using the response surface D-optimal model in the Design-Expert software (version 10.0.2, Stat-Ease Inc., Minneapolis, USA).